The Concept of the Soul (Nafs) in Islamic Philosophy: A Comparative Study of Ibn Sina’s and Ibn Bajjah’s Thought - Muslih, Mohammad Kholid; Kamal, Aria Nur; Faturrahman, Mochammad Eka (Journal of Islamic Thought and Philosophy, 2025)
This study examines and compares the concept of nafs in the works of two prominent Paripatetic Muslim philosophers: Ibn Sina and Ibn Bajjah. Both philosophers played important roles in developing the theory of the soul in the Islamic philosophical tradition. Though their views are often considered to be influenced by Greek philosophy, particularly Aristotelianism, this study seeks to demonstrate that their concept of nafs is an original contribution with a strong foundation in the Qur'an and Sunnah. Using a qualitative approach, the study collects data from the primary works of both figures as well as relevant secondary literature. The analysis reveals key differences between the two philosophers. First, Ibn Sina divides the types of nafs into three: the vegetable soul, the animal soul, and the human soul. In contrast, Ibn Bajjah analyzes the nafs more simply, focusing on its power. Second, regarding the immortality of the nafs, Ibn Sina's view is more comprehensive than Ibn Bajjah's, which limits immortality to the mind and the nafs natiqah. Third, regarding the perfection of the nafs, Ibn Sina emphasizes its perfection as a whole, whereas Ibn Bajjah limits it to the context of active reason.